2016
DOI: 10.1038/gim.2016.22
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotype-driven gene target definition in clinical genome-wide sequencing data interpretation

Abstract: In conclusion, we present a novel approach to a phenotype-driven diagnostic process of genome scale sequencing data that harnesses the sensitivity of these approaches while restricting the analysis to genes relevant to clinical presentation in patient.Genet Med 18 11, 1102-1110.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…According to current European Society of Human Genetics recommendations for whole genome testing in health care, it is preferable to use a targeted gene panel approach first to avoid unsolicited findings or findings that cannot be interpreted . However, the selection of appropriate target genes is challenging and gene panels carry a risk of missing causative variation due to their restrictiveness . Indeed, there are many epilepsy gene panels, with a huge diversity, currently used for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to current European Society of Human Genetics recommendations for whole genome testing in health care, it is preferable to use a targeted gene panel approach first to avoid unsolicited findings or findings that cannot be interpreted . However, the selection of appropriate target genes is challenging and gene panels carry a risk of missing causative variation due to their restrictiveness . Indeed, there are many epilepsy gene panels, with a huge diversity, currently used for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…This was developed using a manual search through OMIM and PubMed databases and a Web tool for phenotype‐based gene panel generation (http://kimg.eu/generator). In our clinical practice, we have used this database‐based bioinformatic panel of 862 genes as a primary filtering system for exome sequencing data and time‐efficient exclusion of both false positive (by filtering out non‐epilepsy‐associated genes) and false negative (by inclusion of epilepsy‐associated genes that could be missed in the whole range of variants) findings. Even though the vast majority of causative variants could be captured by this gene panel, 3 of 42 variants (7%; SOX5 , SCN3A and UBA5 ) were identified during the second stage of untargeted interpretation of exome variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using HPO to generate individualized phenotype-driven gene panels for diagnostics led to an increase in the diagnostic yield (33). The ThromboGenomics Consortium reported that computational prioritization of candidate rare variants identified in patients with bleeding, thrombotic or platelet disorders using HPO-coded phenotypes assigned the highest scores to pathogenic or likely pathogenic variants in 85% of cases, demonstrating that HPO-based algorithms can make multidisciplinary diagnostic meetings more efficient (34).…”
Section: Clinical Utilitymentioning
confidence: 99%